2014
DOI: 10.1155/2014/786892
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characteristics of Chitosan Sponge as a Tissue Engineering Scaffold

Abstract: Cells, growth factors, and scaffolds are the three main factors required to create a tissue-engineered construct. After the appearance of bovine spongiform encephalopathy (BSE), considerable attention has therefore been focused on nonbovine materials. In this study, we examined the properties of a chitosan porous scaffold. A porous chitosan sponge was prepared by the controlled freezing and lyophilization of different concentrations of chitosan solutions. The materials were examined by scanning electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
50
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 49 publications
8
50
0
7
Order By: Relevance
“…Mean pore diameters were determined by analysis of digital SEM images from sectioned samples. Six images (100 different pores) of each sponge were taken and utilized for the mean pore size computation . Transmission electron microscopy (TEM) (JEOL, Japan) was used to observe the morphology of the microemulsion droplets formed after reconstitution with 0.1 N HCl.…”
Section: Methodsmentioning
confidence: 99%
“…Mean pore diameters were determined by analysis of digital SEM images from sectioned samples. Six images (100 different pores) of each sponge were taken and utilized for the mean pore size computation . Transmission electron microscopy (TEM) (JEOL, Japan) was used to observe the morphology of the microemulsion droplets formed after reconstitution with 0.1 N HCl.…”
Section: Methodsmentioning
confidence: 99%
“…Macroporous scaffolds can be formed directly from native CS by freeze‐drying a CS solution in acidic media . The scaffold formed can have interconnected pores and pore sizes ranging from several micrometres to a few hundred micrometres with porosities up to 90% depending on the CS concentration and the freeze‐drying conditions . These materials with sponge‐like characteristics can be named ‘sponges’.…”
Section: Hydrogels Prepared Directly From Native Csmentioning
confidence: 99%
“…At a higher freezing rate, ice crystals have shorter time to grow, and the pore size is thus smaller. However, a decrease in CS concentration leads to an increase in the pore size . Ikeda et al .…”
Section: Hydrogels Prepared Directly From Native Csmentioning
confidence: 99%
“…Although the magnetic excitations in the insulating stripe phase can be described by the linear spin-wave approximation with in-plane anisotropic exchange parameters, a breakdown of the linear spin wave approximation was observed in the magnetic excitations in the checkerboard phase with higher carrier concentration. The spin dynamics in the checkerboard phase of (La 2−x Sr x )NiO 4 (x = 0.5) and more metallic (Nd 2−x Sr x )NiO 4 (x = 0.6, 0.7) are systematically investigated [10]. We found that the observed magnetic excitations in the checkerboard phase do not show counter-propagating spin wave branches up to E ∼ 70 meV as shown in Fig.…”
Section: Experiments In Conventional Energy-momentum Spacementioning
confidence: 88%